Ընտանեկան հարաբերությունների կարգավորման իրավական հիմքերը Սմբատ Սպարապետի «Դատաստանագրքում» - Սարվազյան, Լիլիթ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Известный полководец Киликийского Aрмянского государства, политический деятель, дипломат и законодатель Смбат Спарапет (1208–1276 гг.) в своем «Судебнике» (1265 г.) установил нормы, регулирующие семейные отношения, основываясь на армянском каноническом и обычном праве, а также на «Армянском судебнике» Мхитара Гоша. Смбат стремился сохранить армянскую семью – стабильную основу государства, ее древние традиции и предотвратить разводы. Регулирование семейных отношений принадлежало как светско-государственной, так и духовно- церковной юрисдикции. Smbat Sparapet, an outstanding commander-in-chief, politician, diplomat and legist of the Cilician Armenian State, in his “Code of Law” (1265) established norms regulating family relations, based on the Armenian canonical and customary law, as well as on Mkhitar Gosh’s “Armenian Code of Law”. Smbat’s efforts were aimed at preserving the stability of the Armenian family as the foundation of the state, the ancient traditions, and to prevent divorces. The regulation of family relations was subject to both, secular-state and spiritualecclesiastical jurisdiction.
Keywords: Law; Family relations